Larval exposure to thiamethoxam and pyraclostrobin impairs the morphology of the midgut and Malpighian tubules in newly emerged workers of Scaptotrigona postica (Hymenoptera: Meliponini) - Farder-Gomes, Cliver Fernandes; Bovo, Joyce; da Silva, Jaqueline Aparecida [UNESP]; Gonçalves, Pollyana Leão; Oliveira, Marco Antônio de; Nocelli, Roberta Cornélio Ferreira (Elsevier, 2025)
The indiscriminate use of pesticides to control various pests, including insects and fungi, raises concerns about the potential long-term effects of these toxic substances on pollinators. In this study, we evaluated the effects of larval exposure to the insecticide thiamethoxam and the fungicide pyraclostrobin on the morphology of the midgut and Malpighian tubules in newly emerged Scaptotrigona postica workers. The results revealed that larvae exposed to insecticides, alone and in combination, developed into adult workers with an increased loss of cytoplasmic material in the midgut and Malpighian tubules, suggesting autophagic cell death. The loss of brush border integrity was more pronounced following pesticide treatment, suggesting potential impairment of nutrient digestion and absorption. Cell elimination was observed exclusively in the combination treatment group, indicating a synergistic interaction between the pesticides for this particular effect. These effects result in health impairments in adult bees, potentially compromising pollination services.